Improving Error Correction Stage and Expanding the Final Key using Dynamic Linear-feedback Shift Register in Sarg04 Protocol - Omar Sh. Mustafa; Ali H. Yousif; Dana F. Abdulqadir (Polytechnic Journal)
The mechanism of quantum mechanics is considered as the principal method of quantum key distribution for transmitting a cryptographic key between users in unconditionally secure communication. In this paper, simulation and enhancement of the performance of SARG04 protocol have been done in terms of error correction stage using multiparity rather than single parity. In addition, the suitable length of subblock was selected depending on the values of quantum bit error rate and round number. Dynamic linear-feedback shift register circuits have been used to extend the final key. These circuits are dynamically generated by the final key. A unique linear circuit is created for each generated key.